FUNCTIONAL NANOPARTICLES FOR MOLECULAR IMAGING GUIDED GENE DELIVERY - Liu, Gang (2010)
Gene therapy has great potential to bring tremendous changes in treatment of various diseases and disorders. However, one of the impediments to successful gene therapy is the inefficient delivery of genes to target tissues and the inability to monitor delivery of genes and therapeutic responses at the targeted site. The emergence of molecular imaging strategies has been pivotal in optimizing gene therapy; since it can allow us to evaluate the effectiveness of gene delivery noninvasively and spatiotemporally. Due to the unique physiochemical properties of nanomaterials, numerous functional nanoparticles show promise in accomplishing gene delivery with the necessary feature of visualizing the delivery. In this review, recent developments of nanoparticles for molecular imaging guided gene delivery are summarized.